The invalidity of the argument from illusion - French, Craig; Walters, Lee (University of Illinois Press, 2018)
The argument from illusion attempts to establish the bold claim that we are never perceptually aware of ordinary material objects. The argument has rightly received a great deal critical of scrutiny. But here we develop a criticism that, to our knowledge, has not hitherto been explored. We consider the canonical form of the argument as it is captured in contemporary expositions. There are two stages to our criticism. First, we show that the argument is invalid. Second, we identify premises that can be used to make the argument valid. But we argue that the obvious fixes are problematic. If our arguments are successful, we show that the argument from illusion is even more difficult to defend than is commonly acknowledged.